Calathea multispicata (Marantaceae), a new species endemic to Colombia (2019)
Calathea multispicata H. Kenn. & M. Serna, endemic to Colombia, is described as new. Currently, it is known only from the Department of Valle de Cauca in premontane (1300–1800 m) pluvial forest habitat. Calathea multispicata is characterized by the presence of only two leaves per shoot, one basal and one cauline and the numerous relatively small, short-pedunculate inflorescences. Each inflorescence has 3–4 bracts, which, after the first terminal one, are borne in the axil of the cauline leaf. Calathea multispicata is most similar in aspect to C. harlingii H. Kenn. Calathea multispicata shares the habit of a single cauline leaf subtending inflorescences above one or more basal leaves with C. harlingii, C. hagbergii H. Kenn, C. andersonii H. Kenn. and C. pluriplicata H. Kenn. but differs from these species in having a single vs. 2–10 basal leaves, more numerous (up to 19 vs. 2–7) inflorescences with fewer bracts (3–4 vs. 5–17) borne in a series in the axil of the cauline leaf.